Comparison of the force-, velocity-, and power-time curves recorded with a force plate and a linear velocity transducer. Issue 3 (2nd July 2016) - García-Ramos, Amador; Stirn, Igor; Strojnik, Vojko; Padial, Paulino; De la Fuente, Blanca; Argüelles-Cienfuegos, Javier; Feriche, Belén
Abstract: This study aimed to correlate, compare, and determine the reliability of force, velocity, and power values collected with a force plate (FP) and a linear transducer during loaded jumps. Twenty-three swimmers performed an incremental loading test at 25, 50, 75, and 100% of their own body weight on a FP. A linear velocity transducer (LVT) was attached to the bar to assess the peak and the mean values of force, velocity, and power. Both the peak variables ( r  =  0 .94 – 0.99 for peak force, r  =  0 .83 – 0.91 for peak velocity, and r  =  0 .90–0.94 for peak power; p  <  0 .001) and the mean variables ( r  =  0 .96–0.99 for mean force, r  =  0 .87–0.89 for mean velocity, and r  =  0 .93–0.96 for mean power; p  <  0 .001) were strongly correlated between both measurement tools. Differences in the shape of the force-, velocity-, and power-time curves were observed. The LVT data showed a steeper increase in these variables at the beginning of the movement, while the FP recorded larger values in the latter part. Peak values were more reliable than mean values. These results suggest that the LVT is a valid tool for the assessment of loaded squat jump.